The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1158/1541-7786.mcr-20-0403
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Placental Growth Factor Signaling in Response to Ionizing Radiation Is p53-Dependent and Contributes to Radioresistance

Abstract: Placental growth factor (PlGF) is a pro-angiogenic, N-glycosylated growth factor, which is secreted under pathologic situations. Here, we investigated the regulation of PlGF in response to ionizing radiation (IR) and its role for tumor angiogenesis and radiosensitivity. Secretion and expression of PlGF was induced in multiple tumor cell lines (medulloblastoma, colon and lung adenocarcinoma) in response to irradiation in a dose-and time-dependent manner. Early upregulation of PlGF expression and secretion in re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Integrin β1 sialylation mediated by ST6Gal I contributes to cell adhesion was found to regulate CRC radiotherapy resistance [29]. Moreover, radiotherapy can stimulate CRC tumors to secrete placental growth factor (PlGF), which acts on nonirradiated paracrine tumor cells, resulting in radiotherapy resistance [30]. It was also discovered that patients with high expression of matrix metalloproteinase 1 (MMP1) and matrix metalloproteinase 2 (MMP2) in the ECM of CRC tumor cells developed distant metastases after radiotherapy [31].…”
Section: Tumor Ecmmentioning
confidence: 99%
“…Integrin β1 sialylation mediated by ST6Gal I contributes to cell adhesion was found to regulate CRC radiotherapy resistance [29]. Moreover, radiotherapy can stimulate CRC tumors to secrete placental growth factor (PlGF), which acts on nonirradiated paracrine tumor cells, resulting in radiotherapy resistance [30]. It was also discovered that patients with high expression of matrix metalloproteinase 1 (MMP1) and matrix metalloproteinase 2 (MMP2) in the ECM of CRC tumor cells developed distant metastases after radiotherapy [31].…”
Section: Tumor Ecmmentioning
confidence: 99%
“…Interestingly, not only VEGF but also other pro-angiogenic factors such as placental growth factor (PlGF) are secreted in response to irradiation and in a dose- and time-dependent manner. Our own recent studies showed a strong paracrine vasculature-protective role of PlGF as part of a p53-regulated IR-induced resistance mechanism and suggest PlGF as a promising target for a combined treatment modality with radiotherapy [ 323 ]. Furthermore, not only endothelial cell-directed compounds, but also tumor cell signaling-directed agents may contribute to a window of tumor vasculature normalization, e.g.…”
Section: Radiotherapy and Tumor Hypoxiamentioning
confidence: 99%